EFFECT OF CHAIR AEROBICS AND DANCE MOVEMENT THERAPY ON DEPRESSION, ANXIETY, SLEEP, STRESS, QUALITY OF LIFE AND ASSOCIATED SYMPTOMS IN ELDERLY CANCER PATIENTS: A SINGLE ARM CLINICAL TRIAL - Anushka Pillai; Renu Pattanshetty (Journal of Cancer Rehabilitation, 2022)
Background and objectives A number of physical and psychological issues like pain, depression, anxiety, stress etc. are seen in the elderly cancer patients. Exercise interventions and dance movement therapies have proven to have a positive effect on all of the above mentioned factors in the asymptomatic elderly population. Therefore, this study aimed to assess the effect of chair aerobics and DMT on depression, anxiety, sleep, stress, quality of life and associated symptoms in elderly cancer patients. Materials and Methodology Twenty subjects ≥65 years diagnosed with cancer were included in the study. All the subjects underwent seven sessions of chair aerobics and Dance Movement Therapy daily for one week. Outcome measures used were HADS, PSQI, PSS, ESAS and FACT-G. Results Statistical analysis was done using SPSS version 20. There was statistically significant difference seen in the HADS (p = 0.001), PSQI (p =0.001), PSS (p = 0.001), ESAS (p = 0.01) and FACT-G (p = 0.002) scores. Conclusions The current study demonstrated improvements in terms of reduction in the cancer- associated symptoms, anxiety and depression scores, sleep quality, stress levels and improvement in QOL. This suggests that use of chair aerobics and DMT can be implemented for gaining a holistic recovery for the elderly inpatient cancer population.